Sagrado a photopoetics across the Chicano homeland - Herrera, Spencer R.; Romero, Levi.; Kaiser, Robert; Valdez, Luis (Albuquerque, NM University of New Mexico Press, 2013)
"Robert Kaiser's photographs and Levi Romero's poems find grace in tragedy, elegance in seediness, pride in despair, and moments of joy along the border between the U.S. and Mexico. Spencer Herrera provides narrative context for the photographs and poetry, and together these pieces will form a tightly unified story of the borderlands"--
"Destinations" -- Cuando Vino El Alambre, Vino El Hambre -- "En este pais y en el mio" -- Si Dios quiere -- "Epigraph" -- Dime con Quien Andas ... -- "Like a Good Golden Drink" -- "Still Life #3" -- "turn, turn, turn" -- "Ascension" -- Mi Vida Loca -- "Los Heroes" -- "Familia" -- "No hay honor mas dulce" -- El Norte Mas Alla -- "Taos Nicho" -- "Daddy's Old Trucks" -- "I Breathe the Cottonwood" -- Un Puno De Tierra -- "Years after my father died" -- "Descanso" -- "As It Will Be Without Him" -- Cuando Lleguemos -- "Botes de diez" -- Epilogue: In Search of Pancho Villa -- "Pancho Villa's Prayers".
Includes Bibliographical references
Keywords: Mexican Americans -- Mexican-American Border Region -- Social conditions; Mexican Americans -- Mexican-American Border Region -- Pictorial works; Mexican Americans -- Mexican-American Border Region -- poetry; Mexican Americans Border Region -- social conditions; Mexican Americans Border Region -- Pictorial works; Mexican Americans Border Region -- Poetry